Analysis of Waste Management in the New Angso Duo Market in Jambi City in 2024 - Simarmata, Theresia Hot Sarina; Hidayati, Fajrina; Butar-Butar, Marta; Ridwan, M.; Putri, Fitria Eka (PT FORMOSA CENDEKIA GLOBAL, 2024)
Angso Duo Baru Market, the largest market in Jambi City, contributes 9 tons of waste per day, with 36.37% of the total 291,863.27 tons of waste in Jambi in 2023 coming from the market. This research Analyzes Waste Management in Angso Duo Baru Market in 2024 using descriptive qualitative method. Data were collected from 11 informants through interviews, observations, and document reviews, then analyzed using Nvivo 12 software. The results show that the waste sorting, collection, and processing system is not yet in accordance with Government Regulation No. 27 of 2020. Traders do not segregate waste, and the shelters are not standardized. However, waste transportation is carried out twice a day and the final processing of waste at the Talang Gulo landfill has been carried out properly according to standards.